Araloside C Prevents Hypoxia/Reoxygenation-Induced Endoplasmic Reticulum Stress via Increasing Heat Shock Protein 90 in H9c2 Cardiomyocytes - Du, Yuyang; Wang, Min; Liu, Xuesong; Zhang, Jingyi; Xu, Xudong; Xu, Huibo; Sun, Guibo; Sun, Xiaobo (Frontiers in Pharmacology, 2018)
Araloside C (AsC) is a cardioprotective triterpenoid compound that is mainly isolated from Aralia elata. This study aims to determine the effects of AsC on hypoxia-reoxygenation (H/R)-induced apoptosis in H9c2 cardiomyocytes and its underlying mechanisms. Results demonstrated that pretreatment with AsC (12.5μM) for 12h significantly suppressed the H/R injury in H9c2 cardiomyocytes, including improving cell viability, attenuating the LDH leakage and preventing cardiomyocyte apoptosis. AsC also inhibited H/R-induced ER stress by reducing the activation of ER stress pathways (PERK/eIF2α and ATF6), and decreasing the expression of ER stress-related apoptotic proteins (CHOP and Caspase-12). Moreover, AsC greatly improved the expression level of HSP90 compared with that in the H/R group. The use of HSP90 inhibitor 17-AAG and HSP90 siRNA blocked the above suppression effect of AsC on ER stress-related apoptosis caused by H/R. Taken together, AsC could reduce H/R-induced apoptosis possibly because it attenuates ER stress-dependent apoptotic pathways by increasing HSP90 expression.